Ответ:
1. x² - 6x + 8 = 0
x1 = 4
x2 = 2
2. x²- 2x - 15 = 0
x1 = -3
x2= 5
3. x² - 15x + 36 = 0
x1= 12
x2 = 3
4. z² + 5z + 6 = 0
z1 = -3
z2 = -2
5. y² + 7y - 8 = 0
y1 = -8
y2 = 1
6. y² - 10y - 39 = 0
y1 = 13
y2 = -3
1) а) 2;4 б) -6;1
2) а) -3;5 б) -8;1
3) а) 12;3 б) 13;-3
Объяснение:
1) а) x1 + x2 = 6
x1×x2 = 8
б) x1 + x2 = -5
x1×x2 = 6
2) а) x1 + x2 = 2
x1×x2 = -15
б) x1 + x2 = -7
3) а) x1 + x2 = 15
x1×x2 = 36
б) x1 + x2 = 10
x1×x2 = -39
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
1. x² - 6x + 8 = 0
x1 = 4![\left \{ {{x1 + x2 = 6} \atop {x1 * x2 = 8}} \right. \left \{ {{x1 + x2 = 6} \atop {x1 * x2 = 8}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx1%20%2B%20x2%20%3D%206%7D%20%5Catop%20%7Bx1%20%2A%20x2%20%3D%208%7D%7D%20%5Cright.)
x2 = 2
2. x²- 2x - 15 = 0
x1 = -3![\left \{ {{x1 + x2 = 2} \atop {x1*x2 = -15}} \right. \left \{ {{x1 + x2 = 2} \atop {x1*x2 = -15}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx1%20%2B%20x2%20%3D%202%7D%20%5Catop%20%7Bx1%2Ax2%20%3D%20-15%7D%7D%20%5Cright.)
x2= 5
3. x² - 15x + 36 = 0
x1= 12![\left \{ {{x1 + x2 = 15} \atop {x1 * x2 = 36}} \right. \left \{ {{x1 + x2 = 15} \atop {x1 * x2 = 36}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx1%20%2B%20x2%20%3D%2015%7D%20%5Catop%20%7Bx1%20%2A%20x2%20%3D%2036%7D%7D%20%5Cright.)
x2 = 3
4. z² + 5z + 6 = 0
z1 = -3![\left \{ {{z1 + z2 = -5} \atop {z1 * z2 = 6}} \right. \left \{ {{z1 + z2 = -5} \atop {z1 * z2 = 6}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bz1%20%2B%20z2%20%3D%20-5%7D%20%5Catop%20%7Bz1%20%2A%20z2%20%3D%206%7D%7D%20%5Cright.)
z2 = -2
5. y² + 7y - 8 = 0
y1 = -8![\left \{ {{y1 + y2 = - 7} \atop {y1 * y2 = - 8}} \right. \left \{ {{y1 + y2 = - 7} \atop {y1 * y2 = - 8}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7By1%20%2B%20y2%20%3D%20-%207%7D%20%5Catop%20%7By1%20%2A%20y2%20%3D%20-%208%7D%7D%20%5Cright.)
y2 = 1
6. y² - 10y - 39 = 0
y1 = 13![\left \{ {{y1 + y2 = 10} \atop {y1 * y2 = -39}} \right. \left \{ {{y1 + y2 = 10} \atop {y1 * y2 = -39}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7By1%20%2B%20y2%20%3D%2010%7D%20%5Catop%20%7By1%20%2A%20y2%20%3D%20-39%7D%7D%20%5Cright.)
y2 = -3
Ответ:
1) а) 2;4 б) -6;1
2) а) -3;5 б) -8;1
3) а) 12;3 б) 13;-3
Объяснение:
1) а) x1 + x2 = 6
x1×x2 = 8
б) x1 + x2 = -5
x1×x2 = 6
2) а) x1 + x2 = 2
x1×x2 = -15
б) x1 + x2 = -7
x1×x2 = 8
3) а) x1 + x2 = 15
x1×x2 = 36
б) x1 + x2 = 10
x1×x2 = -39